Cases in the Constitutional Court of Latvia on Language Use in Higher Education: Lessons for Linguists and Decision-makers - Druviete, Ina (Vilnius University Open Series, 2023)
This paper focuses on the cases related to language use in higher education in the Constitutional Court of the Republic of Latvia, specifically about the amendments of the Law on Higher Education Institutions. The ongoing legal dispute pertains to the compliance of the contested norms with several articles of the Constitution of Latvia (Satversme) and the legal norms of the European Union. From a sociolinguistic perspective, the paper analyzes the arguments of the applicants, legislators, and experts involved in the case. The paper draws conclusions about the applicability of the legal process and outcomes for developing a comprehensive theory on how languages can coexist in higher education and research. Additionally, the paper discusses some general considerations about language use in academia and beyond.